Differential gene expression to an LPS challenge in relation to exogenous corticosterone in the invasive cane toad (Rhinella marina). (November 2018) - Gardner, Steven; Assis, Vania Regina; Zhao, Honggang; Gomes, Fernando Ribeiro; Peatman, Eric; Mendonça, Mary T.
Abstract: The cane toad ( Rhinella marina ) is an invasive amphibian in several parts of the world. Much of the research performed on assessing the dispersal potential of invasive species has focused immunity. Invaders are predicted to rely less on pro-inflammatory immunity, allowing them to allocate energy to dispersal. Elevated stress may play a role in regulation of immune responses used by invasive species. RNA sequencing of spleen tissue from cane toads subjected to an acute LPS challenge revealed genes coding for cytokines involved in typical innate responses such as phagocytic cell recruitment, extravasation, inflammation, and lymphocyte differentiation were significantly upregulated, while toads receiving transdermal application of corticosterone in addition to an LPS injection showed downregulation of genes involved with cell mediated immunity. These results indicate hormonal changes associated with acute stress may alter investment into mounting cell-mediated or humoral responses while allowing for prolonged phagocytic innate responses in this invasive species. Highlights: Cane toad expression of immune genes was upregulated following injections with LPS. Primers of cane toad genes allow for quantitative evaluation of gene expression. qPCR validated transcriptomic results of cane toad gene expression. Corticosterone seemingly downregulates genes related to various aspects of immunity.